Assessment of GPR18 pairing with putative cannabinoid ligands - Abdulrazzaq, Ghayth (2018)
GPR18 receptor is a candidate cannabinoid receptor with potential of being a novel therapeutic target due to its wide distribution in various tissues. NAGly which is a metabolite of the first isolated endocannabinoid anandamide, had been suggested by several studies as an endogenous high potency ligand of GPR18 receptor. Yet, some studies have reported the lack of activation of GPR18 by NAGly and some other putative GPR18 cannabinoid ligands. Identifying the signalling mechanism of GPR18 will advance our understanding of the complexity of the endocannabinoid system and may have important implications in determination of the molecular mechanism of action of phytocannabinoids. The rationale of this study was to characterize the pharmacology of GPR18 by investigating the effects of NAGly and other putative GPR18 cannabinoid ligands like THC, Abn-CBD, O-1918 and NARAS on the intracellular signalling mediators, extracellular signal-regulated kinases (ERK1/2) and Ca2+ ions in HEK293TR heterologously expressing GPR18 receptor as well as the cell lines that have been reported in previous studies to express GPR18 endogenously or show biological responses to NAGly namely, mouse microglial cells (BV-2), rat insulinoma β-cell line (INS-1 832/13 β-cells) and human colorectal cancer cells (Caco-2). Changes in the intracellular Ca2+ were also measured following co-expression of GPR18 in Chinese hamster ovarian cell line (CHO) heterologously expressing CB2 and exposure to the GPR18 putative ligands. SNAP-tagged human GPR18 receptor under the control of a tetracycline regulated expression system was heterologously expressed in HEK293TR cells. The effect of putative GPR18 agonists on intracellular Ca2+ mobilisation was assessed using FlexStation and single cell Ca2+ imaging techniques with different Ca2+ probes (fluo-4 and fura-2). NAGly induced ERK phosphorylation was quantified by immunoblotting. The tested panel of cannabinoid ligands did not observed to elicit a significant ligand-mediated phosphorylation of ERK1/2 or mobilisation of intracellular Ca2+ in GPR18-expressing HEK293TR cells, BV-2 cells, INS-1 832/13 β-cells, Caco-2 cells and GPR18-transfected CHO cells heterologously expressing CB2 receptors. In this study recombinant human GPR18 receptor was not activated by NAGly or other cannabinoid ligand suggested by previous studies which indicated that NAGly may be not the natural endogenous ligand of GPR18 and argue against the deorphanization of GPR18 and assignment as a candidate cannabinoid receptor. Also it can concluded that the activation of GPR18 signalling mechanism may involve prodigious pathways not examined in the current study.